Efficacy of neoadjuvant bevacizumab added to docetaxel followed by fluorouracil, epirubicin, and cyclophosphamide, for women with HER2-negative early breast cancer (ARTemis): an open-label, randomised, phase 3 trial. Issue 6 (June 2015) - Earl, Helena M; Hiller, Louise; Dunn, Janet A; Blenkinsop, Clare; Grybowicz, Louise; Vallier, Anne-Laure; Abraham, Jean; Thomas, Jeremy; Provenzano, Elena; Hughes-Davies, Luke; Gounaris, Ioannis; McAdam, Karen; et al.
Summary: Background: The ARTemis trial was developed to assess the efficacy and safety of adding bevacizumab to standard neoadjuvant chemotherapy in HER2-negative early breast cancer. Methods: In this randomised, open-label, phase 3 trial, we enrolled women (≥18 years) with newly diagnosed HER2-negative early invasive breast cancer (radiological tumour size >20 mm, with or without axillary involvement), at 66 centres in the UK. Patients were randomly assigned via a central computerised minimisation procedure to three cycles of docetaxel (100 mg/m 2 once every 21 days) followed by three cycles of fluorouracil (500 mg/m 2 ), epirubicin (100 mg/m 2 ), and cyclophosphamide (500 mg/m 2 ) once every 21 days (D-FEC), without or with four cycles of bevacizumab (15 mg/kg) (Bev+D-FEC). The primary endpoint was pathological complete response, defined as the absence of invasive disease in the breast and axillary lymph nodes, analysed by intention to treat. The trial has completed and follow-up is ongoing. This trial is registered with EudraCT (2008-002322-11), ISRCTN (68502941), andClinicalTrials.gov (NCT01093235 ). Findings: Between May 7, 2009, and Jan 9, 2013, we randomly allocated 800 participants to D-FEC (n=401) and Bev+D-FEC (n=399). 781 patients were available for the primary endpoint analysis. Significantly more patients in the bevacizumab group achieved a pathological complete response compared with those treated with chemotherapy alone: 87 (22%, 95% CI 18–27) of 388 patients in the Bev+D-FEC group compared with 66 (17%, 13–21) of 393 patients in the D-FEC group (p=0·03). Grade 3 and 4 toxicities were reported at expected levels in both groups, although more patients had grade 4 neutropenia in the Bev+D-FEC group than in the D-FEC group (85 [22%] vs 68 [17%]). Interpretation: Addition of four cycles of bevacizumab to D-FEC in HER2-negative early breast cancer significantly improved pathological complete response. However, whether the improvement in pathological complete response will lead to improved disease-free and overall survival outcomes is unknown and will be reported after longer follow-up. Meta-analysis of available neoadjuvant trials is likely to be the only way to define subgroups of early breast cancer that would have clinically significant long-term benefit from bevacizumab treatment. Funding: Cancer Research UK, Roche, Sanofi-Aventis.